Nurses' Experiences of Caring for Older Persons in Transition to Receive Homecare: Being Somewhere in between Competing Values - Sigrun Hvalvik; Bjørg Dale (Nursing Research and Practice)
Older persons in transition to need professional care in their homes will constitute a large group in municipalities in the future. The aim of this study was to obtain insight into nurses' experiences and perceptions of caring for patients in transition to receive homecare. Eleven home nurses divided into two focus groups were interviewed, and a phenomenological hermeneutical design was used. Four interpretations closely related to each other were revealed: it is essential to have an understanding of the patients' transition history; the nurse' repertoire is challenged in the transition process; care must be adapted to the patients' life world; the excellence of care is threatened by the context. The nurses strived to provide care based upon respect for the independent individual as a living whole. Their ambitions were, however, challenged and threatened by the caring context. The cooperation across organizational levels was pointed out as a critical factor with potential for improvement. This must be taken seriously to support the nurses in their endeavors to provide excellent care.